A comparative study on equilibrium scour volume around circular cylinders in clay–sand mixed cohesive beds, at near threshold velocity of sand – an experimental approach. Issue 8 (1st July 2022) - Chaudhuri, Susanta; Pandey, Manish; Debnath, Koustuv; Oliveto, Giuseppe
Abstract: Local scour around a bridge pier is a complex phenomenon resulting from the interaction of the three-dimensional turbulent flow field around hydraulic structures. An accurate estimation of scour depth below the stream-bed is important during design since it determines the foundation levels and the expansion of the bridge foundation structures. The present study reveals the results of flume experiments on equilibrium scour depth and scour volumes around circular bridge pier models in clay–sand sediment mixtures. The scouring process in a cohesive sediment mixture is a complex interaction between clay–sand network structure and bed shear stresses. The bed shear stress reduces inside the scour hole as scour depth increases, and this is related to the different modes of scouring in clay–sand mixtures. An exponential equation for the non-dimensional scour volume is proposed considering all the experimental runs to get a specific understanding of the surrounding volume of scour hole from maximum equilibrium scour depth in a clay–sand mixed cohesive bed, when the approach flow velocity is near to the critical velocity for mixed sand. The proposed equations are validated using the pre-existing data from the literature dealing with experimental investigations on bridge scour using clay–sand mixed cohesive sediment and show good agreement with observed data. HIGHLIGHTS: The present study reveals the results of flume experiments on equilibrium scour depth and scour volumes around circular bridge pier models in clay–sand sediment mixtures. An exponential equation for the non-dimensional scour volume is proposed considering all the experimental runs. The proposed equations are validated using pre-existing data from the literature. Graphical Abstract